Properties of powders produced by electrical explosions of copper-nickel alloy wires; Materials Letters; Vol. 61, № 14-15 - Kwon Y.- S.; An V. V. Vladimir Vilorievich; Ilyin A. P. Aleksandr Petrovich; Tikhonov D. V. Dmitry Vladimirovich (2007, 2007)
Title screen